Reducing Greenhouse Gasses Emission from Energy Consumption in Floating Net Cage Aquaculture (FNCA) - Nurani, Idea Wening; Sunardi, S; Muta'ali, Lutfi; Mei, Estuning Tyas Wulan; Wibowo, Sandy Budi; Fajarwati, Alia; Ridwan, Briantama Yanuar; Maharani, Nooriza; Pradipta, Aditya (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Every sector including aquaculture should be prepared to cope with climate change impacts. Climate change impacts to aquaculture can bring any change to instability of socio-economy and the environment due to its role to support food security, employment and economic growth. Management of aquaculture needs to be modified to face this challenge, not only adaptation efforts but also mitigation efforts. Energy consumption is one of significant source of Green House Gasses (GHG) emission. Therefore, it is necessary to know the detail of energy consumption in aquaculture to find the proper strategy in reducing GHG emission from its operational. This study aimed: (1) to identify sort of energy source used in FNCA; (2) to identify the factors that influences the energy consumption of FNCA. This research was conducted in Cirata Reservoir, West Java Province, Indonesia. This research was conducted in Cirata Reservoir, West Java Province. Quatitative method was applied in this research. The research methodology involved: (1) in depht interview, (2) analysis of existing data through institutional reports and (3) observation. This study showed that: (1) farmers of FNCA in Cirata reservoir consume renewable and non-renewable energy for their daily activities; (2) factors that influence the energy consumption in FNCA are location, operational pattern, number of dwellers, types of boat and electricity sources.